Problems of Musyarakah Account Management in the MSME Sector: A Case Study of Obstacles to Transparency of Customer Financial Reports - Arif, Muhamamd; Sudirman, Wahyu Febri Ramadhan (Journal of Financial and Business, 2026)
This study aims to analyze the problems of Musharakah account management in the Micro, Small, and Medium Enterprises (MSMEs) sector, with a primary focus on constraints regarding customer financial report transparency. As a profit and loss sharing financing instrument, Musharakah relies heavily on the accuracy of real profit reporting, yet its implementation is often hindered by information asymmetry. The research method employed is library research with a qualitative approach, synthesizing data from scientific literature and official financial authority reports within the last ten years. The results indicate that transparency issues are rooted in the low accounting literacy of MSME actors, leading to the inconsistent application of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This condition triggers moral hazard risks in the form of inaccurate profit reporting, which impacts high monitoring costs and Non-Performing Financing (NPF) risks for Islamic banking. Logical interpretation of the findings suggests that digital transformation through cloud-based accounting systems is a strategic solution to create real-time cash flow monitoring. The study concludes that standardizing financial reporting and integrating information technology are absolute prerequisites for building trust in Musharakah partnerships and enhancing MSME accountability within the Islamic financial ecosystem.